A Cerberus-Nodal-Lefty-Pitx signalling cascade controls Left-Right asymmetry in amphioxus - Li, G; Liu, X; Xing, C; Zhang, H; Shimeld, S; Wang, Y (National Academy of Sciences, 2017)
Many bilaterally symmetrical animals develop genetically-programmed left-right asymmetries. In vertebrates this process is under the control of Nodal signalling, which is restricted to the left side of the body by the Nodal antagonists Cerberus and Lefty. Amphioxus, the earliest diverging chordate lineage, has profound left-right asymmetry as a larva. We show that Cerberus, Nodal, Lefty and their target transcription factor Pitx are sequentially activated in amphioxus embryos. We then address their function by TALEN-based knockout and HSP promoter-driven overexpression. Knockout of Cerberus leads to ectopic right-sided expression of Nodal, Lefty and Pitx, while over expression of Cerberus represses their left-sided expression. Overexpression of Nodal in turn represses Cerberus, and activates Lefty and Pitx ectopically on the right side. We also show Lefty represses Nodal, while Pitx activates Nodal. These data combine in a model in which Cerberus determines whether the left-sided gene expression cassette is activated or repressed. We also show these regulatory steps are essential for normal left-right asymmetry to develop, as when they are disrupted embryos may instead form two phenotypic left sides or two phenotypic right sides. Our study shows the full regulatory cassette controlling left-right asymmetry was in place in the ancestor of amphioxus and vertebrates. This includes the deployment of the Nodal inhibitors Cerberus and Lefty, both of which operate in feedback loops with Nodal and combine to establish asymmetric Pitx expression. Cerberus and Lefty are missing from most invertebrate lineages, marking this mechanism as an innovation in the lineage leading to modern chordates.